2019
DOI: 10.1063/1.5110668
|View full text |Cite
|
Sign up to set email alerts
|

Observing large ferroelectric polarization in top-electrode-free Al:HfO2 thin films with Al-rich strip structures

Abstract: We report a large ferroelectric polarization of Al:HfO2 films in metal-ferroelectric-semiconductor structures with a top-electrode free annealing configuration. Annealing an uncapped film at the Al concentration of 7.7 mol. % shows a large remnant polarization up to 50.5 μC/cm2. The film has a unique microscopically laminar distribution of dopant atoms. We find that the formation of the paraelectric monoclinic phase is suppressed in films with laminar distribution. The uniaxial confinement due to the microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…The voltage memory window ΔV g is expressed through the FE remnant polarization P r as [ 16 ]: ΔV g = V Tp− − V Tp+ = 2P r ε 0 ε HAO /δ, where = V Tp− − V Tp+ is the difference of the float band voltages for two polarizations and that coincides with the hole threshold voltage difference (see Figure S7 , Supplementary Materials ), δ is the distance between the charges in the FE insulator and in the channel ~1 nm. Equation (1) gives the value 2 P r = 23 µC/cm 2 , which corresponds to the published results for structures fabricated under similar conditions [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The voltage memory window ΔV g is expressed through the FE remnant polarization P r as [ 16 ]: ΔV g = V Tp− − V Tp+ = 2P r ε 0 ε HAO /δ, where = V Tp− − V Tp+ is the difference of the float band voltages for two polarizations and that coincides with the hole threshold voltage difference (see Figure S7 , Supplementary Materials ), δ is the distance between the charges in the FE insulator and in the channel ~1 nm. Equation (1) gives the value 2 P r = 23 µC/cm 2 , which corresponds to the published results for structures fabricated under similar conditions [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…where = V Tp− − V Tp+ is the difference of the float band voltages for two polarizations and that coincides with the hole threshold voltage difference (see Figure S7, Supplementary Materials), δ is the distance between the charges in the FE insulator and in the channel 1 nm. Equation (1) gives the value 2P r = 23 µC/cm 2 , which corresponds to the published results for structures fabricated under similar conditions [35]. Silicon and hafnia bandgaps (not on the same energy scales for picture clarity) bending at the ferroelectric switching in the symmetric n-SIS structure with the two polarizations down to the substrates (left) and to the Si film (right), the shallow and deep electron traps with the +Q f net trapped charges at the boundaries of ferroelectric stack HfO 2 :Al 2 O 3 (10:1) for the different Si substrate bias voltage V sub : V 0 = -V R , where V R is the residual polarization voltage after/before the P-down switching (left), V 1 = 0 V, V 2 = V R , where V R is the voltage for the coercive switching of polarization (left).…”
Section: Normalized Differential Conductance Approach For the Separation Of Charge Transport Mechanismssupporting
confidence: 71%
“…[9] Other commonly used dopants are Si, [2,[56][57][58] La, [59][60][61][62] Y, [38,[63][64][65] and Al. [66][67][68] Other dopants that have been reported are among others, for example, Sr and Gd. [69][70][71][72][73][74][75][76][77] A major difference between these dopants is their ionic radius.…”
Section: Perovskite and Fluorite Ferroelectricsmentioning
confidence: 99%
“…[ 9 ] Other commonly used dopants are Si, [ 2,56–58 ] La, [ 59–62 ] Y, [ 38,63–65 ] and Al. [ 66–68 ] Other dopants that have been reported are among others, for example, Sr and Gd. [ 69–77 ]…”
Section: Perovskite and Fluorite Ferroelectricsmentioning
confidence: 99%
“…In 2011, T. S. Bo ¨scke et al 12 found the ferroelectricity in noncentrosymmetric orthorhombic hafnium oxide (HfO 2 ) thin film materials prepared by atomic layer deposition (ALD), and silicon-doped HfO 2 also exhibit good ferroelectricity. The novel ferroelectrics in fluorite metal oxides have attracted much attention due to their compatibility with CMOS technology 6,13 and robust remnant polarization with no size effect at the nanoscale (B50 mC cm À2 ), [14][15][16][17] which is significantly higher than that of BTO (B26 mC cm À2 ). 18 Moreover, the low synthesis temperature, good thermal stability and corrosion resistance, 19 higher coercive field 20 and much slower ferroelectric domain moving 21 expand the applications in electronic devices.…”
Section: Introductionmentioning
confidence: 99%